A Novel Six Metastasis-Related Prognostic Gene Signature for Patients With Osteosarcoma - Zheng, Di; Xia, Kezhou; Yu, Ling; Gong, Changtian; Shi, Yubo; Li, Wei; Qiu, Yonglong; Yang, Jian; Guo, Weichun (Frontiers in Cell and Developmental Biology, 2021)
Osteosarcoma is the most common malignant bone tumor, and although there has been significant progress in its management, metastases often herald incurable disease. Here we defined genes differentially expressed between primary and metastatic osteosarcoma as metastasis-related genes (MRGs) and used them to construct a novel six-MRG prognostic signature for overall survival of patients with osteosarcoma. Validation in internal and external datasets confirmed satisfactory accuracy and generalizability of the prognostic model, and a nomogram based on the signature and clinical variables was constructed to aid clinical decision-making. Of the six MRGs, FHIT is a well-documented tumor suppressor gene that is poorly defined in osteosarcoma. Consistent with tumor suppressor function, FHIT was downregulated in osteosarcoma cells and human osteosarcoma samples. FHIT overexpression inhibited osteosarcoma proliferation, migration, and invasion both in vitro and in vivo. Mechanistically, FHIT overexpression upregulate the epithelial marker E-cadherin while repressing the mesenchymal markers N-cadherin and vimentin. Our six-MRG signature represents a novel and clinically useful prognostic biomarker for patients with osteosarcoma, and FHIT might represent a therapeutic target by reversing epithelial to mesenchymal transition.